Synthesis and Characterization Membrane Nanofibers Cellulose Acetate-Zeolite for Metal Pb (II) Adsorption - Intan Dyah Fulanjari; Ervin Tri Suryandari; Hamdan Hadi Kusuma (Jurnal Kimia Sains dan Aplikasi, 2024)
Heavy metal waste, such as lead (Pb), released into the environment negatively affects ecosystems and human health due to its toxic properties. Consequently, it is imperative to develop methods to remove Pb from the environment. One widely used method is adsorption. Synthesizing adsorbents via electrospinning offers several advantages: simplicity, the ability to produce nano-sized fibers, lightness, chemical stability, and reusability. This research aims to determine the optimum conditions for synthesizing cellulose acetate (CA) nanofibers modified with zeolite (CA-Zeolite) by electrospinning to characterize them and evaluate their adsorption capacity. The research results showed that the optimum conditions for the synthesis of cellulose acetate nanofibers were a solution concentration of 14% (w/v), a voltage of 10.5 kV, a flow rate of 0.02 mL/hour, and a tip-to-collector distance of 10 cm. The FTIR spectrum of CA-Zeolite revealed a new peak in the 400-610 cm-1 wavelength range, indicative of O-Si-O bonds, characteristic of zeolite functional groups, confirming the successful incorporation of zeolite into the CA nanofibers. From the SEM data, it can be seen that the addition of 6% (w/w) zeolite reduced the average membrane fiber diameter from 662.4 nm to 353.1 nm. EDX results show the presence of Si and Al elements in the CA-Zeolite nanofiber membrane. Incorporating zeolite into CA nanofibers decreased the contact angle from 125.49° to 111.66°, enhancing hydrophilicity. The modified CA nanofibers with 6% (w/v) zeolite demonstrated an adsorption capacity of 1.595 mg/g.